'ndrangheta and "search for power": reflections on mafia and political power in Australia (Rivista di Studi e Ricerche sulla criminalità organizzata, 2021)
This research is linked to studies on the criminal mobility of the 'ndrangheta in Australia. Starting from extensive research in the field, and from a critique of the concept of ethnicity and its links with organised crime in Australia, this work reflects on the political interests of the Calabrian clans in Australia. Some clans can maintain ties with powers and professional elites also by exploiting "ethnic solidarity” within the migrant community.
Keywords: 'ndrangheta; Australia; mafia mobility; mafia-politics; ethnicity